Rancang Bangun Alat Monitoring Level Air Toren Berbasis Arduino Uno R3 Dan HC-SR04 - Nur’ Aini; Fajerin Biabdillah; Agusma Wajiansyah (Jurnal Publikasi Teknik Informatika, 2026)
Water is an essential resource for human life; however, it is also a limited natural resource that requires proper management, particularly in daily household usage. One common problem encountered is the overflow of water storage tanks (toren) due to negligence, as their elevated placement often makes direct monitoring difficult. This study presents the design and development of an Internet of Things (IoT)-based water level monitoring system for household water tanks using an Arduino Uno R3 microcontroller and an HC-SR04 ultrasonic sensor. The system is designed to measure the water level in real time and display the results on a 16×2 LCD screen. Additionally, visual indicators in the form of red, yellow, and green LEDs are implemented to represent low, medium, and high water levels, providing an intuitive warning system for users. The proposed system aims to prevent water wastage caused by tank overfilling and to improve efficiency in water resource management. Experimental testing shows that the device operates reliably and responsively under various water level conditions. The measurement results indicate that the system is capable of detecting water level changes with an accuracy of approximately ±1 cm. Overall, this monitoring tool offers a simple, low-cost, and effective solution for automatic water level detection and household water conservation.